Bevacizumab in combination with chemotherapy in platinum-sensitive ovarian cancer - Della Pepa, Chiara (Dove Medical Press, 2014)
Targeting angiogenesis is proving to be a successful approach in the management of ovarian cancer. The vascular endothelial growth factor inhibitor, bevacizumab, is the first angiogenesis inhibitor to have shown a significant progression-free survival advantage in the Phase III setting. There is now evidence supporting the use of bevacizumab in combination with chemotherapy for first-line and relapsed (platinum-sensitive and resistant) ovarian cancer. In this review, we summarize the positive Phase III trial (OCEANS [Ovarian Cancer Study Comparing Efficacy and Safety of Chemotherapy and Anti-Angiogenic Therapy in Platinum-Sensitive Recurrent Disease]) that led to European Medicines Agency approval of bevacizumab in platinum-sensitive first relapse and discuss the best use of the drug in this disease.